Engraved on the rocks—Aeolian abrasion of Martian mudstone exposures and their relationship to modern wind patterns in Gale Crater, Mars. (17th June 2020) - Schieber, Juergen; Minitti, Michelle E.; Sullivan, Robert; Edgett, Kenneth S.; Malin, Michael C.; Parker, Tim; Calef, Fred
Abstract: In this contribution we report measurements and interpretations of aeolian abrasion features observed along the Mars Science Laboratory rover traverse at Gale Crater on Mars. Aeolian abrasion of surface rocks has been documented by most missions that have landed on Mars, but attention has largely focused on relatively resistant rocks that display ventifact morphologies well‐known from Earth. The current study instead emphasizes abrasion features developed on mudstone surfaces, because aeolian abrasion textures are very common in the mudstone‐dominated Murray Formation at Gale Crater. These abrasion textures have been observed over a wide area, and they allow deductions about dominant past wind regimes that differ from those observed at present. On Earth, aeolian abrasion features in mudstone outcrops have minimal preservation potential because of the susceptibility of mudstones to moisture and aqueous erosion, even in dominantly arid surface environments. Because of this there is no literature on potential terrestrial analogs. In order to better understand aeolian abrasion morphologies in mudstones on Mars, laboratory experiments were conducted that exposed a range of mudstone samples and rock simulant samples to wind‐driven sand for periods of up to four months. These experiments produced a range of aeolian abrasion textures ('wind tails', fluting, differential 'etching' of laminae, stalks and pedestals) that can serve as analogs for features in the Murray Formation, increasing our confidence regarding aeolian origins for these and the deductions of formative, sand‐driving wind azimuths. Orientations of aeolian abrasion textures along the Mars Science Laboratory traverse were compared with active ripple orientations in rover images, and with previous analyses of orbital images of the study area, in order to evaluate whether the current, complex wind environment can explain the abrasion orientations observed in rover images, or if the abrasion record might also contain signatures of past wind regimes that differed from those of the present. Results show relatively coherent patterns of airflow and sand movement that vary in accordance with factors like local topography and upwind availability of sand for abrasion. Wind events blowing southwest that are primarily responsible for southwest migration of the Bagnold Dunes have also caused bedrock abrasion of similar orientation between these dunes. Less effective wind events (from an abrasion standpoint) blowing south‐southeast have broadly affected bedrock exposures elsewhere across the Mars Science Laboratory landing site away from the Bagnold Dunes. A notable exception are northeast abrasion textures on the more erosion‐resistant sandstones of the Naukluft Plateau. The latter are consistent with one of two abrasion directions measured in previous studies, prior to the rover's arrival at the Murray Formation mudstones, and probably reflect the preservation of an ancient sand‐driving wind regime that differs from that of the present.